Elira for solo, chorus and percussion ensemble - Trangco, Mary Katherine Jakosalem (2013)
This is a story of a woman, Elira, and her journey in finding true love. Her first love, the one she thought would last forever, abruptly ends when the man leaves her for another woman. Her whole world falls apart and she retreats into the darkness of depression. Until ine day, someone befriended her, someone she has never met. He never knew his name for he didn't want to tell her. He insisted that it is enough for her to know that she has a friend who is always beside her. He stayed with her, helped her nurse her broken heart. He listened to her endless ranting about the inequality of life. He kept quite, ever patient and understanding. He accompanied her during the day and left before it was nighttime. Four long years have passed, and Elira has finally broken free from the pains of yesteryears. With this newly found liberty, she realizes that she has fallen in love with the one who has always been with her. She turns to her companion, as if seeing him for the first time. Then she realized that she never knew his name. She demanded he tell her and so he did. I am the moon" he said. Noticing the confusion on Elira's face, he continued explaining his being. "I came down here to be with you." Upon hearing these words, she suddenly felt delighted. According to him, he was given the chance to come down from the skies and be with anyone he chooses during the day and be back to light the path of everyone at night. He further explained that he was never to fall in love for the moon is not for anyone in particular and is for everyone to see and enjoy. Elira then tells him how she feels. And then the moon explains to her that if she doesn't stop what she feels, he would forever be forbidden to come down again. Unable yo fight their feelings, the moon was sent back to the skies leaving Elira with her broken heart.
Thesis (Master in Music) -- University of the Philippines, Diliman.
Keywords: Choruses, Secular with percussion ensembles